An incidental finding of primary carcinoma of the fallopian tube: a case report - Lodha, Nilima D.; Bharati, Kiran S.; Saxena, Neha K.; Hingway, Snehlata R. (International Journal of Research in Medical Sciences, 2016)
Primary fallopian tube carcinoma (PFTC) is a rare malignancy of female genital tract that histologically and clinically resemble epithelial ovarian cancer. Diagnosis of PFTC is difficult, especially at earlier stages. Most of the time it is an incidental finding. Careful surgical and pathological staging is important. It has worse prognosis than ovarian cancer as it is not routinely suspected, hence treatment is delayed. We, hereby, report a rare case of PFTC diagnosed incidentally while doing bilateral salpingoopherectomy for removal of ovarian cyst.